Stakeholders’ expectations and perceived effects of the pharmacy ownership liberalization reform in Sweden: a qualitative interview study - Wisell, Kristin (BMC Health Serv Res, 2016)
BACKGROUND: Reforms in the health-care sector, including the pharmacy sector, can have different rationales. The Swedish pharmacies were prior to 2009 organized in a state-owned monopoly. In 2009, a liberalization of the ownership took place, in which a majority of the pharmacies were sold to private owners. The rationales for this liberalization changed profoundly during the preparatory work, making it probable that other rationales than the ones first expressed existed. The aim of this study was to explore the underlying rationales (not stated in official documents) for the liberalization in the Swedish pharmacy sector, and also to compare the expectations with the perceived outcomes. METHODS: Semi-structured interviews were conducted with representatives from key stakeholder organizations; i.e., political, patient, and professional organizations. The analysis was performed in steps, and themes were developed in an inductive manner. RESULTS: One expectation among the political organization participants was that the ownership liberalization would create opportunities for ideas. The competition introduced in the market was supposed to lead to a more diversified pharmacy sector. After the liberalization, the participants in favor of the liberalization were surprised that the pharmacies were so similar. Among the professional organization participants, one important rationale for the liberalization was to get better use of the pharmacists’ knowledge. However, all the professional, and some of the patient organization participants, thought that the counseling in the pharmacies had deteriorated after the liberalization. As expected in the interviews, the post-liberalization pharmacy sector consists of more pharmacies. However, an unexpected perceived effect of the liberalization was, among participants from all the stakeholder groups, less access to prescription medicines in the pharmacies. CONCLUSIONS: This study showed that the political organization participants had an ideological basis for their opinion. The political stakeholders did not have a clear view about what the liberalization should lead to, apart from abolishing the monopoly. The perceived effects are quite similar in the different stakeholder groups, and not as positive as were expected.